Titanium Dioxide Exposure Induces Acute Eosinophilic Lung Inflammation in Rabbits - CHOI, Gil Soon (Ind Health, 2014)
Titanium dioxide (TiO(2)) is increasingly widely used in industrial, commercial and home products. TiO(2) aggravates respiratory symptoms by induction of pulmonary inflammation although the mechanisms have not been well investigated. We aimed to investigate lung inflammation in rabbits after intratracheal instillation of P25 TiO(2). One ml of 10, 50 and 250 µg of P25 TiO(2) was instilled into one of the lungs of rabbits, chest computed-tomography was performed, and bronchoalveolar lavage (BAL) fluid was collected before, at 1 and 24 h after P25 TiO(2) exposure. Changes in inflammatory cells in the BAL fluids were measured. Lung pathological assay was also carried out at 24 h after P25 TiO(2) exposure. Ground glass opacities were noted in both lungs 1 h after P25 TiO(2) and saline (control) instillation. Although the control lung showed complete resolution at 24 h, the lung exposed to P25 TiO(2) showed persistent ground glass opacities at 24 h. The eosinophil counts in BAL fluid were significantly increased after P25 TiO(2) exposure. P25 TiO(2) induced a dose dependent increase of eosinophils in BAL fluid but no significant differences in neutrophil and lymphocyte cell counts were detected. The present findings suggest that P25 TiO(2) induces lung inflammation in rabbits which is associated with eosinophilic inflammation.